Evaluating the Overall Technical Efficiency of Islamic Banks operating in the MENA Region during the Financial Crisis. - Ali Said (International Journal of Economics and Financial Issues, 2013)
The present paper measured overall technical efficiency of Islamic banks operating in the MENA region during the financial crisis of 2007-2009 to address the question what are the levels of overall, pure technical and scale efficiency of Islamic banks operating in the MENA region and how they evolved during the financial crisis. This paper addresses this question technical, pure technical, and scale efficiency measures are analyzed by employing on-parametric technique, Data Envelopment Analysis (DEA). The study results suggested that Islamic banks in other MENA countries and North Africa on an average are relatively technically inefficient. This might be due to the underdeveloped banking system in those countries. In addition, the decomposition of technical efficiency into pure technical and scale efficiency shows that on average, the Islamic banks in North Africa counties and other MENA counties are having problems in the allocation of resources between their inputs and outputs mix compare to Islamic banks in GCC. Keywords: Islamic banks; DEA; Technical Efficiency; Scale Efficiency; GCC; MENA JEL Classifications: G01; G21; G24; G29